2019
DOI: 10.1111/ene.13946
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of tirofiban combined with endovascular treatment in acute ischaemic stroke

Abstract: Background and purpose Tirofiban is used off‐label in clinical practice for acute ischaemic stroke (AIS). However, it is unknown whether tirofiban increases the bleeding risk or improves the outcome of endovascular treatment (EVT) in AIS. This study evaluated the efficacy and safety of tirofiban in combination with EVT for AIS. Methods Consecutive patients with AIS receiving EVT were included in the prospective stroke registry from 2015 to 2018. The efficacy outcomes were modified Rankin Scale (mRS) score at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 24 publications
1
41
0
Order By: Relevance
“…DOI: 10.1159/000509054 stent retriever trials which confirmed the effect of ET in selected patients with AIS [1][2][3][4][5][6], whereas Kellert et al [13] conducted the study before 2015 and concluded that tirofiban was associated with increased risk of fatal ICH and poor outcome. However, the results of Zhao et al [20] and Pan et al [16], conducted after 2015, were quite the contrary. (2) Discretion of interventionists: the use of tirofiban was at the discretion of interventionists who may be prone to use tirofiban in subjects with heavier atherosclerotic burden and high possibility of reocclusion after the occluded arteries were partially recanaliazed or ultimately achieved good reperfusion.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…DOI: 10.1159/000509054 stent retriever trials which confirmed the effect of ET in selected patients with AIS [1][2][3][4][5][6], whereas Kellert et al [13] conducted the study before 2015 and concluded that tirofiban was associated with increased risk of fatal ICH and poor outcome. However, the results of Zhao et al [20] and Pan et al [16], conducted after 2015, were quite the contrary. (2) Discretion of interventionists: the use of tirofiban was at the discretion of interventionists who may be prone to use tirofiban in subjects with heavier atherosclerotic burden and high possibility of reocclusion after the occluded arteries were partially recanaliazed or ultimately achieved good reperfusion.…”
Section: Discussionmentioning
confidence: 90%
“…We retrieved 1,213 articles that were potentially pertinent. After removing duplicates and reviewing titles and abstracts to exclude irrelevant studies, case reports, and reviews, 11 cohort trials [10][11][12][13][14][15][16][17][18][19][20] fulfilled all the inclusion criteria and included 2,028 patients ( Fig. 1).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to multivariate regression analysis, tirofiban was not associated with the risk of sICH and mortality at 3-month. Several previous studies also observed that endovascular treatment (EVT) alone has no absolute superiority over tirofiban combined with EVT in terms of safety (1012, 15). Moreover, two recent studies that assessing the safety of abciximab (another approved GP IIb/IIIa inhibitors) combined with EVT concluded that abciximab treatment may be relatively safe (16, 17).…”
Section: Discussionmentioning
confidence: 98%